Covid-19 from basics to clinical practice - Zhang, Wenhong (World Scientific Publishing, 2020)
"This book introduces the epidemiological characteristics, etiology, molecular biology, virology and the latest research progress of COVID-19. It also presents the clinical manifestations, diagnosis and treatment of the new infectious disease. The content is based on literature review of a large number of relevant articles published in China and abroad, as well as the experience of medical workers in this field in China. In the pandemic, experts from major hospitals in Shanghai had successfully treated more than 300 patients with COVID-19. Their valuable experience in diagnosis and treatment has been summarized and included in the book. It is hoped that this book will be helpful to the vast number of readers who are concerned about the research progress and treatment of COVID-19.